Social communication in bats - Chaverri Echandi, Gloriana (2018)
Bats represent one of the most diverse mammalian orders, not only in terms of species numbers, but also in their ecology and life histories. Many species are known to use ephemeral and/or unpredictable resources that require substantial investment to find and defend, and also engage in social interactions, thus requiring significant levels of social coordination. To accomplish these tasks, bats must be able to communicate; there is now substantial evidence that demonstrates the complexity of bat communication and the varied ways in which bats solve some of the problems associated with their unique life histories. However, while the study of communication in bats is rapidly growing, it still lags behind other taxa. Here we provide a comprehensive overview of communication in bats, from the reasons why they communicate to the diversity and application of different signal modalities. The most widespread form of communication is the transmission of a signaller's characteristics, such as species identity, sex, individual identity, group membership, social status and body condition, and because many species of bats can rely little on vision due to their nocturnal lifestyles, it is assumed that sound and olfaction are particularly important signalling modes. For example, research suggests that secretions from specialized glands, often in combination with urine and saliva, are responsible for species recognition in several species. These olfactory signals may also convey information about sex and colony membership. Olfaction may be used in combination with sound, particularly in species that emit constant frequency (CF) echolocation calls, to recognize conspecifics from heterospecifics, yet their simple structure and high frequency do not allow much information of individual identity to be conveyed over long distances. By contrast, social calls may encode a larger number of cues of individual identity, and their lower frequencies increase their range of detection. Social calls are also known to deter predators, repel competitors from foraging patches, attract group mates to roost sites, coordinate foraging activities, and are used during courtship. In addition to sound, visual displays such as wing flapping or hovering may be used during courtship, and swarming around roost sites may serve as a visual cue of roost location. However, visual communication in bats still remains a poorly studied signal modality. Finally, the most common form of tactile communication known in bats is social grooming, which may be used to signal reproductive condition, but also to facilitate and strengthen cooperative interactions. Overall, this review demonstrates the rapid advances made in the study of bat social communication during recent years, and also identifies topics that require further study, particularly those that may allow us to understand adaptation to rapidly changing environmental conditions.